A New Design for Linear Phase FIR Digital Filter with Efficient Realization - Abdul-Jabbar, Jassim M.; Abood, Afaf A. (Basrah Journal for Engineering Sciences, 2009)
In this paper, the design of linear phase FIR digital filter using Frequency Sampling method is presented. Such design is achieved with a reduction in the maximum stop-band ripples utilizing optimal transition-band sample value throughout the use of Golden Section search method for single transition samples, and with aid of Steepest Descent method for double transition samples. The realization requirements of such filters are reduced by the use of a new analytic design. The reduction can be increased to 50% of the whole filter structure. Therefore, the designed FIR filter offers global properties, minimum stop-band, minimum pass-band, average deviation, and reduced structure complexity.